Bioefficacy and safety evaluation of newer insecticides and acaricides against chilli thrips and mites - Varghese, Thania Sara; Mathew, Thomas Biju (Journal of Tropical Agriculture, 2013)
The bioefficacy of newer insecticides against the sucking pests of chilli and safety of these insecticides to natural enemy population in chilli ecosystem were evaluated at College of Agriculture, Vellayani, Thiruvananthapuram, Kerala. Spiromesifen 45 SC at 100 g a.i. ha-1 and propargite 57 EC at 570 g a.i. ha-1 were found to be effective in reducing chilli mite population whereas acetamiprid 20 SP at 20 g a.i. ha-1 along with spiromesifen were found to be effective against chilli thrips. The leaf curling symptom due to the feeding of mites and thrips was least in spiromesifen, propargite and acetamiprid sprayed plants. Spiromesifen was found to be the safest insecticide against natural enemies viz. predatory mites, coccinellid beetles, spiders and neutral insects whereas the organophosphate insecticide dimethoate 30 EC 300 g a.i. ha-1 was found to be unsafe to natural enemies.